Research trends on health issues and the role of women entrepreneurs from the United Nations Climate Change Conferences - De-las-Heras-Jambrino, Carlos; Rando-Cueto, Dolores; De-las-Heras-Pedrosa, Carlos (My University, 2025)
Climate change is considered one of the greatest threats to health and quality of life. International cooperation initiatives, such as the United Nations Climate Change Conferences (COP), aim to promote solutions to this situation. These include proposals for female entrepreneurship, which seek alternatives to mitigate climate change and ensure the well-being of women, as the group with the highest poverty rates and most dependent on threatened natural resources. The objective of this study is to describe the evolution of research on aspects related to climate change and health carried out at the COPs and to analyse the relevance of women entrepreneurs in the scientific literature on international meetings
Keywords: Cambios climáticos - Aspectos sociales; Mujeres en el desarrollo; Naciones Unidas; Climate change; United Nations Conferences Communication; Female entrepreneurship health